Options for Treatment-Resistant Depression - Vinall, Maria (MD Conference Express, 2009)
Only about 50% of patients with major depressive disorder will respond after their first treatment, and of these responders, only 50% to 70% will achieve symptom remission [Rush AJ et al. Am J Psychiatry 2003]. This article discusses several pharmacological strategies that are used in patients whose depression is resistant to treatment after optimized monotherapy has been attempted, as well as several of the somatic treatments that are emerging as options.